2013
DOI: 10.1371/journal.pone.0078821
|View full text |Cite
|
Sign up to set email alerts
|

Do Treatment Quality Indicators Predict Cardiovascular Outcomes in Patients with Diabetes?

Abstract: BackgroundLandmark clinical trials have led to optimal treatment recommendations for patients with diabetes. Whether optimal treatment is actually delivered in practice is even more important than the efficacy of the drugs tested in trials. To this end, treatment quality indicators have been developed and tested against intermediate outcomes. No studies have tested whether these treatment quality indicators also predict hard patient outcomes.MethodsA cohort study was conducted using data collected from >10.000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Out of 7698 combined search results, 53 articles were identified that reported at least 1 measure of therapeutic inertia in the management of hyperglycaemia in individuals with type 2 diabetes . The main reasons for exclusion of publications other than duplicates and those covering irrelevant topics were that they reported non‐original research (eg, editorials, letters, comments and guidelines) or they were congress abstracts (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Out of 7698 combined search results, 53 articles were identified that reported at least 1 measure of therapeutic inertia in the management of hyperglycaemia in individuals with type 2 diabetes . The main reasons for exclusion of publications other than duplicates and those covering irrelevant topics were that they reported non‐original research (eg, editorials, letters, comments and guidelines) or they were congress abstracts (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies were carried out in Asia, and a single study was conducted in Israel . Articles mainly reported data from cohort studies, using data from medical records or chart reviews, or from claims, clinical research or administrative databases. Four articles reported results from cross‐sectional studies, and the data were collected using provider questionnaires or surveys .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations